Impact of comprehensive geriatric assessment on treatment decisions in older prostate cancer patients - Maëva Bonneau; Zara Steinmeyer; Mathilde Morisseau; Stéphanie Lozano; Patricia Barbe; Catherine Chauvet; Delphine Brechemier; Loïc Mourey; Laurent Balardy (BMC Cancer)
Abstract Background Prostate cancer is the most common cancer in men aged above 75 years old. Given their heterogeneity, the International Society of Geriatric Oncology recommends using a comprehensive geriatric assessment (CGA) to adapt anticancer treatment management according to their geriatric status. While the theoretical value of this approach is in no doubt, the impact of the CGA on the final therapeutic decision remains elusive. This study therefore investigated the impact of comprehensive geriatric assessment on treatment decisions in older patients diagnosed with prostate cancer and described the factors associated with a change in treatment plan. Methods This single-centre retrospective study included prostate cancer patients who received a CGA prior to a therapeutic decision from January 2012 to December 2022. The CGA included medical, nutritional, cognitive, social, functional and psychological evaluation. Results 140 patients were included, of whom 57 (40.7%) benefited from a change in their therapeutic plan after CGA, all in favour of a less aggressive treatment. There was no difference in event-free (EFS) or overall survival (OS) between patients with or without a therapeutic modification (HR for OS = 1.12 [0.68;1.84] p = 0.048). Factors associated with a change in treatment plan were a WHO performance status > 1, a high age-adjusted Charlson score, polymedication, an impaired functional independence with the ADL (Activities of Daily Living) scale and a ‘frail’ or ‘vulnerable’ geriatric profile according to Balducci’s classification. Conclusion A comprehensive geriatric assessment prior to prostate cancer treatment plan initiation lead to therapeutic de-escalation in 40% of cases of without affecting overall survival or event-free survival. This adaptation offering a more tailored cancer management while preventing functional impact of treatment due to toxicity and improving patient quality of life. Trial registration The study was registered as (number’s register: F20240123102237) and MR004 (CNIL number: 23RDUROL01).